Serum Cytokine Analysis Reveals Predictors of Progression from Chronic Hepatitis B to Liver Cirrhosis - Cai, F; Zhao, Y; Chen, Q; Hu, Y; Su, S; Lu, Y (Folia biologica (Praha), 2021)
Hepatitis B virus (HBV) infection is more likely to develop into chronic and persistent infection in China, which is the main cause of chronic liver disease. We examined the cytokine profiles of chronic hepatitis B (CHB) and CHB-caused liver cirrhosis (LC) to look for the predictor of progression from CHB to LC. Serum samples of 15 healthy controls (HC), 15 CHB patients and 15 LC patients were collected to detect the profiles of 48 cytokines by multiplex biometric ELISA-based immunoassay. Partial least squares discriminant analysis (PLS-DA) and random forest were used to analyse significant cytokines, which were further validated by ELISA using an independent cohort of 60 CHB patients, 60 LC patients and 35 HC samples. There were 18 differentially expressed cytokines of CHB and LC. Three cytokines were identified by PLS-DA and random forest, including interleukin (IL)-9, granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-2 receptor subunit α (IL-2Rα), which displayed significant changes in serum levels. Differentially expressed cytokine networks between HC, CHB and LC also indicated particular cytokine co-expression network patterns of CHB and LC. The receiver-operator characteristic (ROC) analysis demonstrated that IL-9, GM-CSF, IL-2Rα and their logistic regression panel are potential predictors that significantly differentiate CHB from LC (P < 0.001) and CHB from Child class A LC (P < 0.001). The three cytokines and the panel showed significant correlation with the Child-Pugh score. IL-9, GM-CSF, IL-2Rα and their logistic panel may be predictors for monitoring the progression of CHB to LC.
Keywords: virus hepatitidy B; Hepatitis B virus; Liver Cirrhosis; cytokiny; China; Cytokines; Hepatitis B, Chronic; Čína; chronická hepatitida B; lidé; jaterní cirhóza; Humans